Apport de la génétique pour une meilleure connaissance des populations naturelles et une amélioration des populations cultivées d'huîtres plates et creuses - Lapegue, Sylvie (2007)
In the framework of the French diploma "Habilitation à Diriger des Recherches", Sylvie Lapègue's synthesis of research includes ten years (1998-2007) of work in bivalve genetics, and mainly cupped and flat oysters. This research has been developed in (1) flat oyster population genetics at the European level and cupped oyster populations and species genetics at a global scale, (2) the characterization of a cytogenetic particularity observed in oysters that corresponds to a high rate of aneuploidy in somatic cells, and (3) more recently in the use of molecular markers for the construction or improvement of genetic maps, allowing (4) the identification of areas of the genome related to the resistance to summer mortality in the Pacific oyster and the resistance to the parasite responsible for bonamiosis in the European flat oyster. This research has achieved many scientific advances, some of which can be used in the management of the genetic diversity of natural or cultivated populations, in the genetic improvement through breeding programs, or in a better understanding of the genetic architecture of characters of interest such as resistance to diseases. La synthèse du travail de recherche dans le cadre de l'Habilitation à Diriger des Recherches de Sylvie Lapègue regroupe dix années (1998-2007) de travaux en génétique des mollusques bivalves et principalement des huîtres, creuses et plates. Cette activité de recherche s'est développée autour de (1) la génétique des populations d'huîtres plates au niveau européen et des populations et espèces d'huîtres creuses au niveau mondial, (2) la caractérisation d'une particularité cytogénétique des huîtres qui correspond à un fort taux d'aneuploïdie dans les cellules somatiques, puis (3) plus récemment sur l'utilisation de marqueurs moléculaires pour la construction ou l'amélioration de cartes génétiques, permettant de (4) détecter de zones du génome respectivement liées à la résistance aux mortalités estivales chez l'huître creuse et la résistance au parasite responsable de ...